Nursing staff's experience of appearance issues in various nursing situations - Åsa Bringsén; Johanna Sjöbeck; Pia Petersson (BMC, 2021)
Abstract Background Health care professionals frequently interact with unknown patients in a process involving appearance-based judgements and priority-setting, all of which has an effect on health care equality. The healthcare provider-patient interaction is also highly relevant for the awareness and support of patients' appearance concerns, with an associated possibility for improving patients' satisfaction with their appearance and health. The aim was therefore to explore nursing staff's experience of patients' appearance issues in various nursing situations, with the purpose to facilitate awareness raising and knowledge development. Method A qualitative research approach with focus group interviews was chosen due to the exploratory aim of the study. Five semi-structured focus group interviews were conducted with 24 nursing staff in total (19 women and five men). The participants' ages varied (20 to 45 years) as did their professional nursing experience. The interviews lasted approximately one hour, were digitally recorded, transcribed verbatim and analysed through thematic analysis. Results The thematic analysis resulted in the two themes Patient perspective and Professional nursing role, with associated subthemes. The findings showed the importance and impact of appearance issues in nursing situations and how these are linked to the health of the patients. Some groups of patients were identified as more vulnerable than others, which was associated with health care inequalities and health disparities. Value-based strategies along with knowledge, and skills for holistic person-centred care were identified as important resources for the development of appearance-related awareness and support in various nursing situations. Conclusion Strategies for improvement can be realised through the educational system for nursing staff, but mainly by using collective reflective learning forums in different workplaces. An empowerment approach is considered a useful framework for the implementation of holistic person-centred care, functioning as a resource for appearance-related awareness and support in various nursing situations. However, more research is needed on the complex and challenging phenomenon of appearance issues in nursing situations. Knowledge development related to successful person-centred strategies for appearance-related awareness and support is important, especially strategies with a salutogenic perspective.